(3MGTjI Ydi TQM edNU GdLZejfi dbGVi RGOg GdQheis - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3fMeOc jGef LYdJ GdCQV egGOkG hHYO , aEf HgGA GdOjf eMeO GdYGedi jbhd TQM GdeHMK GdeTJgQ ai GdCbWGQ TQM GdLZejfi ddeMbb GdQhei ahLOJg bO Mbb GdebGe hhKb GdcdGe Ydi hLg dGeRjO Ydjg s
(3BNQgG (B:s
(3hbO CaQW GdTQGM GdaGVd ai GdJTfjY Ydi Pjfc GdeMbbjf ceG JQi hbO YQaJ eeG JdhfGg Ydjc Cf JTfjYg efYcS Ydjg,hHVGYJg eQOhOI Edjg , hCf GdeMbbjf GdePchQjf HQjFGf ef GdZadI hGdEgeGd , hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdfSNI ebGHdIs
(3HgG fXGe GdJYbjHIs
(3HgG LOGhd hCTcGds
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs